Reforming Fossil Fuel Subsidies : Drivers, Barriers and the State of Progress - Rentschler, Jun; Bazilian, Morgan (Taylor and Francis, 2017)
This article outlines the current state of affairs in fossil fuel subsidy reform, and highlights its contribution at the nexus of climate policy, fiscal stability and sustainable development. It discusses common definitions, provides quantitative estimates, and presents the evidence for key arguments in favour of subsidy reform. The main drivers and barriers for reform are also discussed, including the role of (low) oil prices and political economy challenges. Commitments to subsidy reform by the international community are reviewed, as well as the progress at the country level. Although fossil fuel subsidy reform indeed plays a critical role in climate policy, experience shows that the rationale for such reforms is determined in a complex environment of political economy challenges, macro-economic, fiscal and social factors, as well as external drivers such as energy prices. The article synthesizes the key principles for designing effective reforms and emphasizes that subsidy reforms cannot only yield fiscal relief, but should also contribute to long-term sustainable development objectives. Areas for future research are also identified.